Pengaruh Keunikan dan Bauran Pemasaran Jasa terhadap Kepuasan Konsumen Boogie Doogie Cafe - Julio Intan Thomas; Vina Meliana (UNIVERSITAS KALBIS, 2022)
This study aims to determine the effect of the uniqueness and marketing mix of services on Boogie Doogie Cafe consumer satisfaction. There are two variables in this study, namely the uniqueness of the product and the service marketing mix. Researchers used quantitative methods and the samples used in this study amounted to 100 respondents who are customers of Boogie Dogie Cafe. The technique used in this study is purposive sampling which is part of non-probability sampling. The research data analyzed using SPSS 23 shows that the uniqueness and marketing mix of service variables influence the Boogie Doogie café consumer satisfaction.